Comparison of low fixed dose versus standard-dose rituximab to treat thrombotic thrombocytopenic purpura in the acute phase and preemptively during remission. (December 2020) - Reddy, Manasa S.; Hofmann, Sandra; Shen, Yu Min; Nagalla, Srikanth; Rambally, Siayareh; Usmani, Amena; Sarode, Ravi
Abstract: The standard dose of rituximab used in B-cell hematological malignancies, 375 mg/m 2 weekly, may be excessive for autoimmune conditions. Successful use of a low, fixed dose of 100−200 mg of rituximab, weekly for 4 weeks, has been reported in the literature in the treatment of autoimmune thrombotic thrombocytopenic purpura (aTTP). We retrospectively analyzed our rituximab data in aTTP over a 13-year-period for 39 patients, with the aim of comparing response and outcomes with a standard lymphoma-dose course versus a low fixed 100 mg-dose course. Compared to the standard dose (17 patients, 17 courses of 4 infusions), our patients who received a low dose (8 patients, 9 courses of 4 infusions) had a possibly lower baseline risk but did achieve a similar time to remission and number of plasma exchange procedures to remission. Preemptive low-dose courses for ADAMTS13 activity <50 % during remission (6 patients, 10 courses of 4 infusions) achieved a median peak ADAMTS13 activity of 99 %, in a median of 1 month, with no clinical relapses. Our results provide additional evidence for the efficacy of low-dose rituximab, with the benefit of much lower cost, less infusion time, and theoretically lower risk of toxicity.